Jeduxiaoliu Formula can Induce Apoptosis of Lymphoma Cells In Vitro and In Vivo - Feng, XiaoWei; Hu, Ming; Wei, Cong Ming; Zhang, Hong Yu; Jiang, Wen Wen; Hu, Qi (Combinatorial Chemistry & High Throughput Screening, 2025)
ObjectiveLymphoma is the most common malignancy of the haematological system. Jeduxiaoliu formula (JDXLF) exerts good therapeutic effects against lymphoma, however, the mechanisms underlying these effects remain unclear. Therefore, this study aimed to investigate the mechanism of action of JDXLF.MethodsRNA-Seq was performed to examine the molecular mechanisms underlying the therapeutic effects of JDXLF against lymphoma. CCK-8 assay was performed to examine the effects of JDXLF on the proliferation of lymphoma cells. Electron microscopy was performed to examine the morphology of lymphoma cells. Flow cytometry was performed to examine the apoptosis and cell cycle of lymphoma cells. qPCR and Western blotting were performed to detect the expression of apoptotic genes and proteins. In vivo, the tumour-suppressive effect of JDXLF on lymphoma transplanted tumours was examined by establishing a subcutaneous transplantation tumour model in nude mice, and the expression of apoptotic proteins in tumour tissues was analysed via immunohistochemical staining.ResultsRNA-Seq revealed 71, 350 and 620 differentially expressed genes (DEGs) in the 1 mg/mL, 4 mg/mL and 8 mg/mL JDXLF treatment groups, respectively. KEGG pathway analysis showed that the DEGs were significantly associated with apoptosis, TNF signalling and NF-κB signalling. In vitro experiments revealed that JDXLF inhibited the proliferation of lymphoma (Raji and Jeko-1) cells in a dose-dependent manner, induced apoptosis and upregulated the expression of Bax/Bcl2 and caspase3. In vivo experiments revealed that JDXLF had a significant tumour-shrinking effect on mice and increased the expression of the apoptosis-related proteins caspase3 and Bax/Bcl2.ConclusionsThis study indicates that JDXLF can induce apoptosis in lymphoma cells in vitro and in vivo. We suggest this may provide a direction for further research into lymphoma therapy.
Keywords: apoptosis